Implementation of Talaqqi Method in Learning Tahfidz Al-Qur'an at At Taqwa Putri Islamic Boarding School Bekasi - Waliko, Waliko; Arinasti, Meivika Nurlisa; Nurkamiden, Syukrin; Ismatulloh, A.M. (AJIRSS: Asian Journal of Innovative Research in Social Science, 2022)
The similarities are that they both use the Talaqqi method in their application. The angel Gabriel also used the Talaqqi method when conveying revelations to the Prophet Muhammad. Then the difference lies in the target in applying the Talaqqi method were at the At-Taqwa Putri Islamic Boarding School. Thus, the Talaqqi method can be the most appropriate solution to be applied among the At-Taqwa Putri Islamic Boarding School students. In 1986, a higher level was established, namely the At-taqwa Putri Islamic Boarding School. The target is all At-Taqwa Putri Islamic Boarding School students, both tahfidz and non-tahfidz. The Al Baqiyatussalihat Islamic Boarding School changed its name to the At-taqwa Putri Islamic Boarding School. With the Talaqqi method, the Qur'an is not only preserved verbally and in writing but also how to read it. Advantages and Disadvantages in the application of Talaqqi Method in At-Taqwa Putri Islamic Boarding School. The At-taqwa Putri Islamic Boarding School, originally named Pesantren al Baqiyatussalihat. The author has observed tahfidz students at At-Taqwa Putri Islamic Boarding School Bekasi and found that in implementing the memorization process using the Talaqqi method. Talaqqi Method at At-Taqwa Putri Islamic Boarding School. In this activity, there were findings as reported by TQ informants for the muraja'ah process of tahfidz students usually doing it independently or making halaqah with an unspecified time and anywhere. Talaqqi method. This research was conducted by direct interviews with students and the general chairman of the student organization at At-Taqwa Putri Islamic Boarding School Bekasi. Meanwhile, this research focuses specifically on one method, namely the Talaqqi method.